2008
DOI: 10.1002/mrc.2238
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of the diterpene mulin‐11,13‐dien‐20‐oic acid by Mucor plumbeus

Abstract: Two new mulinane-type derivatives: 16-hydroxy mulin-11,13-dien-20-oic (2) acid and 7alpha,16-dihydroxy mulin-11,13-dien-20-oic (3) acid were obtained by microbial transformation of mulin-11,13-dien-20-oic acid (1), along with tyrosol (4) using liquid cultures of Mucor plumbeus. The latter compound has not been previously identified in the genus Mucor. Structural elucidation of these metabolites was achieved using 1D- and 2D-NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
8
0
2
Order By: Relevance
“…The relative configuration of 1 was assigned by NOESY experiments. A NOE correlation observed between H-9 and H 3 -17 indicated that the rings B/ C must be cis-fused, which is in agreement with the stereochemistry of mulinane-type diterpenoids [4,[6][7][8]. Based on these findings, we assigned the structure of 1 as mulin-12-en-16-al-20-oic acid.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The relative configuration of 1 was assigned by NOESY experiments. A NOE correlation observed between H-9 and H 3 -17 indicated that the rings B/ C must be cis-fused, which is in agreement with the stereochemistry of mulinane-type diterpenoids [4,[6][7][8]. Based on these findings, we assigned the structure of 1 as mulin-12-en-16-al-20-oic acid.…”
supporting
confidence: 78%
“…have been extensively used in Ayurveda, Unani, homeopathic, and traditional Chinese medicine systems [4,5]. Previous chemical investigation reported many oleanane triterpenoids from the bark of T. arjuna and the fruits of T. chebula, some of which possess antioxidant, antitumoral, antiallergic, antiasthmatic, antifeedant, and cardioprotective activities [6][7][8][9][10][11][12]. Continuing to search chemical markers for the quality control study of the two Terminalia species, two new oleanane triterpene glucosyl esters, ajunglucosides IV (1) and V (2) (l " Fig.…”
mentioning
confidence: 99%
“…Некоторые аналоги мулин-11,13-диен-20-овой кислоты содержащиеся в растении Azorella compacta обладают антиплазмоидной активностью [Loyola et al, 2004]. Гриб Mucor plumbeus IMI 116688 в растущей культуре за 15 суток превращал мулин-11,13-диен-20-овую кислоту (CCCXVI) в два метаболита: 16гидроксимулин-11,13-диен-20-овую кислоту (CCCXVII, выход 0.8 %) и 7α,16-дигидроксимулин-11,13-диен-20овую кислоту (CCCXVIII, выход 0.75 %) [Areche et al, 2008]:…”
Section: CCCXVunclassified
“…Mulinanes [15][16][17][18][19][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Structurally, these compounds (or nearly of all them) are characterized by having an acid group in C-20, and a seven-member ring C functionalized. They show a wide variety of biological activities, such as antituberculosis, antimalaric, antibacterial, spermatostatic, and antihyperglycemic effects ( Table 5.3).…”
Section: Mulinanes and Azorellanesmentioning
confidence: 99%